Analysis of Non-Performing Loans in PT. Bank Rakyat Indonesia (Persero) Tbk, Unit Lubuk Begalung 2019-2020 - Dety Lafera (DINASTI RESEARCH, 2021)
Banks in general, in carrying out their operations to obtain business results, are always faced with a risk. One of the risks experienced by a bank is the large ratio of non-performing loans or what is called Non-Performing Loans/NPLs. Based on Bank Indonesia regulations, a bank has a dangerous potential if the bank has an NPL ratio of more than 5%. This study aims to analyze the level of non-performing loans at PT. Bank Rakyat Indonesia (Persero) Tbk Lubuk Begalung Padang Unit in 2019-2020. This research was conducted using quantitative methods. The data used in this study are the total number of loans (BRIGuna, KUPEDES, KUR) and the number of loans experiencing problems (BRIGuna, KUPEDES, KUR) in 2019-2020. This study uses trend analysis as a data analysis tool. From the results of a partial analysis, BRIGuna's NPL level for 2019-2020 was 0, respectively, in very healthy conditions and 15.62% in unhealthy conditions. BRIGuna's NPL increased by 156% in 2019-2020. The KUPEDES NPL level for 2019-2020 is 5.35% for unhealthy conditions and 2.15% for healthy conditions respectively. KUPEDES's NPL decreased in 2019-2020 by 59.82%. BRIGuna's NPL increased by 156% in 2019-2020. The KUR NPL rate for 2019-2020 was 4.04% each. with fairly healthy conditions and 2.07% with healthy conditions. KUR NPLs decreased in 2019-2020 by 48.74%.